2021
DOI: 10.1111/mec.16292
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements mark a repeat‐rich region associated with migratory phenotypes of willow warblers (Phylloscopus trochilus)

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 77 publications
2
20
0
Order By: Relevance
“…This role in helping the species adapt to environmental conditions was similarly discovered for fish diadromy, which is the migration between freshwater and the sea, in a study that investigated genomes of 24 fish species ( Carotti et al, 2021 ). Similar adaptions have also been observed for the migratory phenotype of birds such as willow warblers ( Caballero-López et al, 2022 ), and in the relationship between sociality and genomic architecture in snapping shrimps, Synalpheus ( Chak et al, 2021 ). Further, ancestral state construction suggested that TEs propagated the transition to eusociality ( Chak et al, 2021 ).…”
Section: Systematic Functions Of Transposable Elementssupporting
confidence: 67%
“…This role in helping the species adapt to environmental conditions was similarly discovered for fish diadromy, which is the migration between freshwater and the sea, in a study that investigated genomes of 24 fish species ( Carotti et al, 2021 ). Similar adaptions have also been observed for the migratory phenotype of birds such as willow warblers ( Caballero-López et al, 2022 ), and in the relationship between sociality and genomic architecture in snapping shrimps, Synalpheus ( Chak et al, 2021 ). Further, ancestral state construction suggested that TEs propagated the transition to eusociality ( Chak et al, 2021 ).…”
Section: Systematic Functions Of Transposable Elementssupporting
confidence: 67%
“…2 a and 3 ). Unlike the InvP-Ch1 and InvP-Ch5 that are chromosomal inversions the MARB-a is a repeat-rich block with a varying copy number of a specific TE 15 . Thus, our present genotyping protocol can only score for absence (<7 copies of TE) or presence (>7 copies of TE) of MARB-a (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In total, we retrieved data from 72 individuals of which 51 are from the migratory divide. Each bird was blood sampled upon recapture and genotyped for InvP-Ch1, InvP-Ch5 16 and presence or absence of MARB-a 15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between DNA sequence variation and epigenome variation is likely complicated by variants that are difficult to detect or quantify. For example, copy number variants and transposable element insertions may be important and inheritable DNA sequence variants, but detecting these remains difficult particularly in non-model organisms (Caballero-Lopez et al, 2021). When these undetected sequence variants are important to a measured phenotype and co-vary with epigenome variants, this may give the false impression that the trait is solely epigenetically inherited; if this happens frequently across the genome this will, perhaps falsely, suggest that sequence variation is not strongly related to epigenetic variation (Heard and Martienssen, 2014).…”
Section: Does Dna Sequence Diversity Relate To Epigenome Diversity An...mentioning
confidence: 99%